Tandem acceptorless dehydrogenative coupling-decyanation under nickel catalysis - Midya, Siba P.; Subaramanian, Murugan; Babu, Reshma; Yadav, Vinita; Balaraman, Ekambaram (Journal of Organic Chemistry, 2021)
The development of new catalytic processes based on abundantly available starting materials by cheap metals is always a fascinating task and marks an important transition in the chemical industry. Herein, a nickel-catalyzed acceptorless dehydrogenative coupling of alcohols with nitriles followed by decyanation of nitriles to access diversely substituted olefins is reported. This unprecedented C=C bond-forming methodology takes place in a tandem manner with the formation of formamide as a sole byproduct. The significant advantages of this strategy are the low-cost nickel catalyst, good functional group compatibility (ether, thioether, halo, cyano, ester, amino, N/O/S heterocycles; 43 examples), synthetic convenience, and high reaction selectivity and efficiency.